Implementasi Tat Twam Asi Pada Pendidikan Karakter Anak Di Masa Pandemi Covid-19 - Desak Ketut Angraeni (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2022)
Tat Twam Asi Application on Children's Character Education During the Covid-19 Pandemic ABSTRACT Corona Virus Disease 2019 or what we often call Covid-19 is a disease that has attacked the human respiratory system since the end of 2019 causing a worldwide pandemic. The Indonesian state itself has implemented the New Normal or a new life with new habits by following health protocols, namely, being obliged to use a mask while doing activities outside of the house, washing hands or using a hand sanitizer after holding something and keeping a distance from people around. This pandemic certainly affects various sectors, especially the education sector. In the world of education, students are required to carry out online learning at home which is assisted by teachers and parents. With the restrictions on large-scale activities, interactions between people are reduced, so that it has an impact on the formation of good character for children, which should be formed at school and at home when they enter early childhood education to high school level. Good character in children can be reflected in the teachings of Hinduism, one of which is Tat Twam Asi which is the basis of Hindu Ethics in an effort to achieve moral improvement. Tat Twam Asi means it is you, meaning that the position as fellow human beings is the same. Applying Tat Twam Asi teachings to students at home and online learning during the Covid-19 pandemic can form good characters in respecting and loving parents, friends, teachers, local residents and the surrounding environment so that they can create a peaceful atmosphere in the family and harmony among others.